Association of lubricin concentration in synovial fluid and clinical status of osteoarthritic knee. Issue 3 (4th May 2017) - Ogawa, Hiroyasu; Matsumoto, Kazu; Terabayashi, Nobuo; Kawashima, Kenji; Takeuchi, Kentaro; Akiyama, Haruhiko
Abstract: Objectives : Although lubricin plays a role in controlling inflammation and pain as well as being a mechanical lubricant, clinical relevance of lubricin concentration in synovial fluid (SF) is unknown. The purpose was to determine whether lubricin concentration in SF is associated with the clinical status of the knee. Methods : SF was obtained from 61 knee joints from patients who underwent any knee surgery with several stages of knee osteoarthritis. Lubricin/PRG4 concentration in SF was measured by enzyme-linked immunosorbent assay (ELISA). Clinical evaluations of the knee by the Kellgren and Lawrence (K–L) system, Knee Society Score (KSS), and the range of knee motion, and assessment of joint laxity were performed. Association of lubricin concentration in SF and these clinical factors was statistically analyzed. Results : There was no significant correlation between lubricin concentration in SF and age, sex, K–L grade, or KSS. However, lubricin concentration was significantly correlated with anteroposterior laxity ( R = 0.50, p < 0.001), full flexion angle ( R = 0.39, p < 0.01), and range of knee motion ( R = 0.38, p < 0.01), but not full extension angle, varus laxity, or valgus laxity. Conclusions : Lubricin concentration was correlated with joint flexibility, but not with clinical symptoms, including pain at that time.